Analisis fluktuasi jumlah produksi gula tebu perbandingan bertahap triangular fuzzy inference system - Ratna Ekawati (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2021)
Sugar production owned by PT X (Persero) for the last 10 years still shows fluctuation. One of the factors is climate, including rainfall. Judging from the development, sugarcane is still vulnerable to the climate. Even so, there are still strategies to reduce the resulting risks, including by means of an appropriate cropping system. However, the safety stock of raw materials cannot be maintained because the quality of the sugarcane deteriorates very quickly. Therefore, sugarcane is continuously sourced in varying quantities and qualities from hundreds of geographically dispersed varieties and supplied to the milling process and due to changing weather conditions so that throughout the year, the time window must be considered for harvesting. Fuzzy logic is a science of uncertainty that has superior ability to process reasoning in language. In fuzzy logic theory, it is known that the concept of fuzzy systems is used in the prediction process and generally contains four stages: fuzzification, formation of fuzzy rules, fuzzy inference system reasoning, and defuzzification. Variable rainfall (mm/year), average yield (%/year), total sugarcane production (million tonnes/year) based on a triangular model of incremental uncertainty as an information attribute in the Fuzzy Inference System (FIS). The selection obtained by using the fuzzy inference system is approximately 5 points from the uncertainty factor that arises from the effect of the input on the total output of the resulting sugar cane production.